Stabilization of fluoroindate glasses by magnesium fluoride and other heavy metal fluorides - Costa, B. J. (1998)
Indium fluoride-based glasses constitute a new generation of materials for applications in the midinfrared spectral range. Their extended transparency in the IR makes them attractive for use as optical fibers for CO laser power delivery and optical amplification. This paper firstly describes the spectacular stabilizing effect of MgF2 on the binary system InF3-BaF2. The investigation of the InF3-BaF2-MgF2 system led to samples up to 5mm in thickness. Further optimization of this system was achieved by incorporation of limited amounts of other fluorides and resulted in increased resistance to devitrification. The second approach of this work was concerned to the investigation of the pseudo-ternary system InF3-GdF3-GaF3 at constant concentrations of ZnF2-SrF2-BaF2-NaF. Several compositions were studied in this system. The samples presented a better thermal stability when compared to other families of fluoride glasses. Therefore, these glasses seem to be very promising for the fabrication of special optical fibers. Thermal data are reported.